Hubungan antara Self-Disclosure Remaja Awal dan Persepsi Remaja Awal terhadap Komunikasi Suportif Orang Tua - Margo, Celeste; Shanti, Theresia Indira (JURNAL KONSELING GUSJIGANG, 2020)
Appropriate support can be provided by parents if early adolescents self-disclose from parents. However, through self-disclosure, early adolescents also need to perceive their parents as individuals who are able to accept their self-disclosure and are able to provide support. Therefore, parents need to show supportive communication that can encourage the desire of adolescents to perform self-disclosure. The purpose of this study is to see whether there is a significant relationship between early adolescent’s self-disclosure and early adolescent’s perception of supportive parental communication. The participants of this study were 614 early adolescents within the age range of 13-15 years who had undergone education, living with both parents, and domiciled in Jakarta. The participants were obtained through a non-probability sampling method by convenience sampling technique. To answer the purpose of this study, The Jourard Self-Disclosure Questionnaire and the Parental Supportive Communication Scale were used to conduct a correlation test. The correlation test results indicate that there is a significant positive relationship between early adolescent’s self-disclosure and early adolescent’s perception of supportive parental communication. For future research, the researchers outlined some important suggestions to be considered.